Pengaruh Technical Factors dan Reliability Factors Terhadap Pengguna Software Sistem Keuangan Desa di Kabupaten Karawang - Neneng Wahyuningsih; Dene Herwanto; Wahyudin Wahyudin (Fakultas Teknik, 2023)
This research was conducted to analyze the effect of Technical Factors and Reliability Factors on the Perceived e-Readiness of the Village Financial System (Siskeudes) variable in Karawang Regency, as well as to analyze the influence of the Intention to Use variable on the Actual Adoption Software Village Financial System (Siskeudes) variable. This study uses Technical Factors and Reliability Factors with 5 variables that affect Perceived e-Readiness of Siskeudes software including the variables Perceived Simplicity, Technical Quality of Service, Accessibility, Perceived Trust and Regulation and Policies which are processed using the Structural Equation Modeling (SEM) method with SmartPLS 3.0 program assistance. Data collection was carried out by distributing questionnaires (questionnaires) to 297 villages, especially village officials in Karawang regency who already use the village financial system (Siskeudes). The results of this study indicate that the variables Perceived Simplicity, Technical Quality of Service, Accessibility, Perceived Trust and Regulation and Policies have a significant positive effect on the Perceived e-Readiness variable, while the Perceived e-Readiness variable has a positive and significant effect on the Intention to Use variable. and the Intention to Use variable has a significant effect on the Actual Adoption Software variable.